The Positive Effect of Behavioral Contract Techniques on Children's Discipline - Devi, I Gusti Ayu Fitria; Jampel, I Nyoman; Antara, Putu Aditya (Universitas Pendidikan Ganesha, 2022)
The discipline of children who have not been maximized indicates a lack of reinforcement of the moral and discipline aspects from an early age. This study analyzes the behavior contract technique on children's discipline attitudes. This research is a pre-experimental research type One group Pre-test-Post-test. The population of this study was children in group B, with four children as samples who were given treatment. The sampling technique in this study used a purposive sampling technique. Data analysis through descriptive statistics includes mean, median, mode, standard deviation, and variance; inferential statistics include normality, homogeneity, and t-test. The results of the Pre-test normality test were obtained < (0.381). It was accepted, and the Post-test normality test was obtained < (0.381) it was accepted. The homogeneity test results = 1.8 < 9.28, categorized as homogeneous. Hypothesis test results t-count = 9, smaller than the t-table that is 2.446. This shows that H0 is rejected and H1 is accepted. It is a finding that explains the influence of behavior contract techniques on children's discipline. Thus, the behavior contract technique positively affects the child's disciplinary behavior. This research implies that the behavioral contract technique is appropriate as an alternative to stimulate disciplinary behavior in early childhood.